Helicobacter pylori CagA: From Pathogenic Mechanisms to Its Use as an Anti-Cancer Vaccine - Stein, Markus; Ruggiero, Paolo; Rappuoli, Rino; Bagnoli, Fabio (Frontiers in Immunology, 2013)
Helicobacter pylori colonizes the gastric mucosa of more than 50% of the human population, causing chronic inflammation, which however is largely asymptomatic. Nevertheless, H. pylori-infected subjects can develop chronic gastritis, peptic ulcer, gastric mucosa-associated lymphoid tissue (MALT) lymphoma, and gastric cancer. Chronic exposure to the pathogen and its ability to induce epithelial-to-mesenchymal transition (EMT) through the injection of CagA into gastric epithelial cells may be key triggers of carcinogenesis. By deregulating cell-cell and cell-matrix interactions as well as DNA methylation, histone modifications, expression of micro RNAs, and resistance to apoptosis, EMT can actively contribute to early stages of the cancer formation. Host response to the infection significantly contributes to disease development and the concomitance of particular genotypes of both pathogen and host may turn into the most severe outcomes. T regulatory cells (Treg) have been recently demonstrated to play an important role in H. pylori-related disease development and at the same time the Treg-induced tolerance has been proposed as a possible mechanism that leads to less severe disease. Efficacy of antibiotic therapies of H. pylori infection has significantly dropped. Unfortunately, no vaccine against H. pylori is currently licensed, and protective immunity mechanisms against H. pylori are only partially understood. In spite of promising results obtained in animal models of infection with a number of vaccine candidates, few clinical trials have been conducted so far and with no satisfactory outcomes. However, prophylactic vaccination may be the only means to efficiently prevent H. pylori-associated cancers.